Solid Tumor in Children: A Single Centre Experience (Sir Salimullah Medical College Journal, 2022)
Introduction: Now a days, number of childhood tumors are gradually increasing throughout the world. But in Bangladesh we have no actual tumor register. In this study we just try to find out the demographic presentation of solid tumor in a tertiary care center of Dhaka city.Methods and materials: it is a retrospective descriptive type of observational study. Study was held in department of pediatric surgery, Sir Salimullah medical college Mitford hospital Dhaka from January 2016 to December 2020.Results: total number of the patients were 37. Male 15 and female 22. Male female ratio is 1:1.7. Age range of the patients from 9 days to 13 years. Mean age 135.83 days. Among 37 patients, 29 had malignant tumors and rest of 8 patients had benign tumor. Ovarian tumors were highest, 10. Then nephroblastoma 9, neuroblastoma 7, non Hodgkin lymphoma 3, sacrococcygeal teratoma 3, adrenal benign tumor 1, soft tissue sarcoma in pelvis 1, rhabdomyosarcoma of urinary bladder1, rectal carcinoma 1 and rhabdomyosarcoma of lower limb 1 accordingly. Most of the patients were went through surgery first then sent for chemotherapy according to histology.Conclusion: In spite of a tertiary medical care center in Dhaka city, our number of patient is not satisfactory. Lack of proper awareness in public, lots of patient did not reach to proper center, those who attained hospital, may lost. And our poor record keeping system is also responsible for adequate informations.Sir Salimullah Med Coll J 2021; 29(2): 117-120